Analisis Faktor Penerimaan Media Internet sebagai Sumber Informasi Kesehatan dengan Model UTAUT dan HBM - Heru Widianto; Ahmad R Pratama; Rahadian Kurniawan (STMIK Budi Darma, 2021)
People are increasingly turning to the internet for health-related information. It is very easy to perform or obtain health-related services or information on the internet using different types of devices. This study's goal is to assess public acceptance of the internet as a source of health information by combining the Unified Theory of Acceptance and Use of Technology (UTAUT) with the Health Belief Model (HBM). SEM techniques were used to analyze data collected from 324 respondents via online questionnaires. Two factors from the HBM model: self efficacy (SE) and cues to action (CA) were found as the strongest factors behind the acceptance of the internet as a source of health information. Two other factors from UTAUT model; Social Influence (SI) and Performance Expectancy (PE) also had significant effects, albeit not as strong, on the acceptance of internet media as a source of health information. This study's findings also point to the possibility of incorrect self-medication when excessive perceived self-efficacy (SE) is combined with symptoms as cues to action (CA) and social influence (SI) when looking up health information online